Analisis Rencana Anggaran Biaya Pada Bangunan Gedung Student Center Universitas Atma Jaya Yogyakarta - Putri Jea, Maria Carvallo; Sari, Sely Novita; Hermawan, Anggi (ReTII, 2023)
Cost estimation is a critical aspect of project execution, serving to ascertain the necessary funding for construction. This research centers on the Estimated Budget Plan (Rencana Anggaran Biaya or RAB) for the construction of Atma Jaya University Yogyakarta’s Student Center Building. Its primary objective is to determine the comprehensive cost for the building’s construction. Adhering to the SNI No. 1 of 2022 guidelines, the research employs a combination of primary and secondary data collection methods, drawing from sources like Plan Drawings, the Unit Price of Goods and Services (SHBJ), and Unit Price Analysis Guidelines. Subsequently, the research involves several key steps, including quantifying the volume of each type of work, assessing unit prices for these tasks, formulating the budget plan, and concluding with a comprehensive summary of costs for each category of work. Microsoft Excel is the tool of choice for these budget plan calculations. The analytical process encompasses volume computations, unit price assessments, and the final RAB, yielding a total cost estimate of Rp 71,899,735,842.00 for the construction of the Student Center Building at Atma Jaya University Yogyakarta.